Импедансная модель прецизионных платиновых термометров сопротивления в области высоких температур - Михаль, А.А.; Мелещук, Д.В. (Технічна електродинаміка, 2012)
Double-pole multiunit impedance model of sensitive thermometer element during measurement on alternating current is proposed. It takes into consideration impact on resistance of sensitive element of bypassing effect which is caused by essential lowing of specific resistance of framework isolation elements with temperature growth. As a result, during the measurement of thermometer resistance on direct and alternating current the error appears which is the function of measurable temperature and current frequency. Theoretical investigations of frequency error of thermometers in the range of temperatures from 0 to 1100 °C are conducted. Difference in the results of measurement of resistance of major types of thermometers is established which leads to the error of 0,1-0,2 mK. Model analysis demonstrates the necessity for introduction of individual frequency correction to the measurement result like correction for zero power of dispersion.